Disaster of university ranking - Abd Razak, Dzulkifli (2009)
ON Oct 8, 2009, when the results of the THESQS ranking was announced, I was in Giessen, about an hour from Frankfurt, to fullfil an invitation by the European University Association (EUA), the main umbrella of all universities in the continent. The invitation was in conjunction with a conference, entitled "Internationalisation beyond European frontiers" and I was asked to present my views, from the perspective outside Europe, as one of the two main speakers. The other was the Rector of Berlin Free University, one of the oldest and renown university in Germany, in fact, Europe too.